2017
DOI: 10.1099/ijsem.0.002085
|View full text |Cite
|
Sign up to set email alerts
|

Domibacillus mangrovi sp. nov. and Domibacillus epiphyticus sp. nov., isolated from marine habitats of the central west coast of India

Abstract: While studying culturable bacterial diversity in different marine habitats of the central west coast of India, two novel Gram-stain-positive, strictly aerobic, motile, endospore-forming and rod-shaped bacterial strains designated as SAOS 44T and SAB 38T were isolated from mangrove sediment soil and the surface of a macroalga, respectively. The strains were taxonomically characterized by using a polyphasic approach and genomic methods. The phylogenetic analysis based on 16S rRNA gene sequencing placed the strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…? oxidation , Domibacillus (Firmicutes), a gram-positive, spore-forming, aerobic, nonmotile, rod-shaped organism isolated from deep-sea sediment (Sun and Sun 2016), ocean sediment (Sharma et al 2014), mangrove sediment soil and macroalgae (Verma et al 2017) and GP1 (Acidobacteria), found in alpine grassland on the Tibetian Plateau (Yuan et al 2014). Winter samples were more characterized by extremophile but omnipresent bacteria like Bifidobacterium (Actinobacteria) that can withstand a high range of pH (from 8 to 2) (Charteris et al 1998), Vulcaniibacterium, a thermotolerant Gammaproteobacteria isolated from a geothermally heated soil (Yu et al 2013), and Polaribacter (Bacteriodetes), which has been found in several arctic habitats (Cuthbertson et al 2017;Harding et al 2011;Collins et al 2010).…”
Section: Different Seasonal Dispersal Patterns For Bacterial and Fungmentioning
confidence: 99%
“…? oxidation , Domibacillus (Firmicutes), a gram-positive, spore-forming, aerobic, nonmotile, rod-shaped organism isolated from deep-sea sediment (Sun and Sun 2016), ocean sediment (Sharma et al 2014), mangrove sediment soil and macroalgae (Verma et al 2017) and GP1 (Acidobacteria), found in alpine grassland on the Tibetian Plateau (Yuan et al 2014). Winter samples were more characterized by extremophile but omnipresent bacteria like Bifidobacterium (Actinobacteria) that can withstand a high range of pH (from 8 to 2) (Charteris et al 1998), Vulcaniibacterium, a thermotolerant Gammaproteobacteria isolated from a geothermally heated soil (Yu et al 2013), and Polaribacter (Bacteriodetes), which has been found in several arctic habitats (Cuthbertson et al 2017;Harding et al 2011;Collins et al 2010).…”
Section: Different Seasonal Dispersal Patterns For Bacterial and Fungmentioning
confidence: 99%
“…Apart from the above-described ones, there is also a less abundant representation of some environmental-associated taxa, many of which have been isolated from varied environments such as Deinococcus, Domibacillus, Pantoea or Sphingomonas [57][58][59][60]. Others have been linked to isolated cases of fungaemia, bacteremia or sepsis, such as Aureobasidium, Kosakonia, Lysinibacillus or Massilia [61-64].…”
Section: Discussionmentioning
confidence: 99%
“…For chemotaxonomic analysis, freeze-dried cells were prepared by growing in TSB+ASW for 2 days at 30 °C. The respiratory quinone of strain D1-1 T and its closely related taxa were extracted using the procedure described by Verma et al [33]. Briefly, 100 mg freeze-dried cells were incubated with 2 ml aqueous methanol and 2 ml light petrol (BP; 60-80 °C) in Teflon-lined screw cap tubes.…”
Section: Halomonas Desiderata Fb2 T (Nr026274)mentioning
confidence: 99%